Village-flouting, adages, and fashion differences among villages: an example of Fonó, Gölle, Kisgyalán, and the surrounding villages - Lanszkiné Széles, Gabriella (Acta Scientiarum Socialium, 2011)
Village-flouting, adages, and fashion differences among villages: an example of Fonó, Gölle, Kisgyalán, and the surrounding villages. The population of villages has made no secret of their views about other communities; either it was a good or a bad judgment. Opinions formed of each other enhanced togetherness within their own village. The awareness of differing from the other village – manifested in fashion or action – created a strong connection between community members. The willingness to overtake the neighboring village expressed ambition and skills to advance. The aim of the data collection was to introduce folk costumes, wandering stories and the economy of villages based on village-flouting. Even altercations and fights evolved from mockery in the beginning of the last century; but nowadays these are devoted to the benefit of villages. Today, history is more valued, celebrations are held in honor to village-flouting, village chorus protect their folk costumes. With collaboration, the traditions of the past live on.
Keywords: village-flouting; folk costume; wandering stories; anecdote; commonality; hostility; tradition